One year's study of growth and total hydroxyproline excretion in scoliotic children. Issue 6 (June 1980) - Clark, S; Harrison, A; Zorab, P A
Abstract : 21 children with scoliosis were studied for a year during which time 24-hour urinary total hydroxyproline levels are estimated and anthropometric measurements were made on 4 occasions. The total hydroxyproline levels (using hydroxyproline centiles) and the uncorrected heights of the children were all normal. The sitting heights of the children were below average, but, although the sample was small, the findings indicate that the children's 'uncoiled' height would be greater than average.